KESALAHAN UMUM vs MISKONSEPSI DINAMIKA: ANALISIS PEMAHAMAN KONSEP GAYA DALAM FISIKA - Riris Idiawati; Ferdiana; Izza Afkarina (JEAS (Journal of Educational and Applied Science), 2025)
The purpose of this article is to examine the possible causes of student error in explaining various physical phenomena, mainly due to lack of ability in understanding the physics concept. Unlike the misconception theory, resource theorists believe that studenterrors are more due to their incomplete understanding less frequently observed by researchers, especially in Indonesia. An in-depth study of the causes of student error is very important to be used as a reference as a design of quality learning. In this article will examine students difficulties in understanding the force conceptaccording to the perspective of resource theory, as well as learning alternatives to reduce errors.